KEHADIRAN PARTAI GELOMBANG RAKYAT INDONESIA SEBAGAI MANAJEMEN KONFLIK INTERNAL PARTAI POLITIK - Muhammad Sidiq; Robi Cahyadi Kurniawan; Arizka Warganegara; Fitria Barokah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Conflict within political parties is something that cannot be avoided, and not infrequently internal conflicts can create party divisions. This paper aims to analyze how the internal conflict of the PKS party can give birth to a new party (Gelora). This paper uses a literature study, with the data used being books and primary or original scientific reports contained in articles or journals related to internal conflicts of political parties and the institutionalization of political parties. Based on the results of the analysis, this paper explains that the birth of the Gelora party was due to differences in political ideology between Anis Matta and Hilmi Aminudin, and the reforms that Anis Matta wanted were rejected by PKS cadres. Seeing the institutionalization of the Partai Keadilan Sejahtera (PKS) is still relatively low because the party cannot overcome its own internal conflicts, thus creating divisions and giving birth to a new party (Partai Gelora). The form of conflict management taken by the conflicting parties is by establishing a new party, namely Gelora. In other words, the conflict of action will continue internally, because there are parties who decide to break up the party.